The crystal structure of 2-(4-fluorophenyl)-1,3,4-oxadiazole, C8H5FN2O - Zhou Zhixu (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C8H5N2O, monoclinic, P21 (no. 4) a = 7.892(8) Å, b = 6.088(6) Å, c = 15.701(16) Å, β = 90.08(3)°, V = 754.4(13) Å3, Z = 4, Rgt(F) = 0.0423, wRref(F2) = 0.1032, T = 273 K.